EFEKTIVITAS PEMBERIAN PHOTOPERIOD YANG BERBEDA PADA MEDIA PEMELIHARAAN LARVA IKAN PAPUYU (Anabas testudineus) TERHADAP LAJU PERTUMBUHAN DAN KELANGSUNGAN HIDUP - Reni Reni; Leni Handayani (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
The purpose of this study was to determine which photoperiod affects the growth and survival of papuyu (Anabas testudineus) larvae. The research was conducted on Jl. Dr. Wahidin Sudiro Husodo Kuala Pembuang I for 6 weeks. The larvae used in this study were 3 days old with a stocking density of 20 fish/tub, the larvae were reared with different lighting durations for 27 days. The lighting treatment was carried out using lights installed in each treatment equipped with a switch with a power of 5 watts, then each aquarium was given black plastic so that the light effect from other treatment lamps did not affect other aquariums. Feeding was carried out by means of satiation feeding with the type of fengli flour feed size 0. This study used 4 treatments and 3 replications, namely treatment A: 24T:0G, B: 16T:8G, C: 8T: 16G and D: 0T: 24G. Research parameters include larval growth and fish survival and water quality as supporting data. Based on the results of the study, a good photoperiod for growth rate and survival is 24 hours of light, 0 dark. While the results of the analysis of giving different photoperiods to papuyu fish larvae had no effect on absolute weight growth but on length growth showed a very real effect, while for the survival of fish larvae there was no effect on the treatment.